Feasibility of local anesthesia for full-endoscopic spine surgery: A retrospective cohort study of body weight-based thresholds - Takafumi Ohshima; Takayuki Kitahara; Seiya Watanabe; Saori Soeda; Daiki Nakajima; Hiroshi Kageyama; Masatoshi Morimoto; Hiroaki Manabe; Fumitake Tezuka; Junzo Fujitani; Atsushi Teramoto; Koichi Sairyo (PLoS ONE, 2026)
Background While transforaminal full-endoscopic spine surgery (TF-FESS) under local anesthesia offers the advantages of real-time neurological feedback and minimized physiological stress, concerns persist regarding whether the procedure can be consistently completed within safe local anesthetic dosage limits in all patient populations. This study evaluated the feasibility and safety of TF-FESS under local anesthesia independent of frailty status using body weight-based safety thresholds for lidocaine. Methods We retrospectively identified 108 patients who underwent single-level TF-FESS under local anesthesia and categorized them into a non-frail group (modified Frailty Index-5 [mFI-5] < 2, n = 80) and a frail group (mFI-5 ≥ 2, n = 28). Weight-based thresholds, calculated using actual body weight, were set at 7 mg/kg for non-frail patients and 5 mg/kg for frail patients. The anesthesia protocol consisted of sequential 1% lidocaine injection and conscious sedation. Complications were defined as clinically significant local anesthetic systemic toxicity, postoperative delirium, and permanent nerve root injury, with exclusion of transient intraoperative feedback. Results Surgery was successfully completed under local anesthesia in all 108 cases (100%), with continuous verbal communication maintained throughout the procedure. The mean lidocaine dose was 218 ± 40 mg, with no significant difference between groups (p = 0.722). In the frail group, 92.9% of patients remained within the stricter 5 mg/kg threshold. No documented cases of clinically significant local anesthetic systemic toxicity, permanent nerve root injury, or postoperative delirium were observed in either group. Conclusions TF-FESS under local anesthesia appears feasible, with no clinically significant complications observed in this cohort, irrespective of frailty status. Although the dosing thresholds were well-tolerated, they should be interpreted with caution given the study’s retrospective nature. Adherence to weight-based dosing and a standardized conscious sedation protocol is associated with a favorable safety profile while preserving real-time neurological feedback. This strategy may minimize perioperative physiological stress and cognitive risks in an increasingly aging population.